Web Results

Solve this equation: y/9+5=0 - Mathfiles.com

www.mathfiles.com/view.php/927.doc

Solve this equation: y/9+5=0. Since y/9+5=0, we get. y/9=-5. So,. y=9*(-5)=-45. If five times a number plus two is 17, what is the number? We have. 5x+2=17.

Equation Factoring Calculator -- Algebra.Help... (y + 9)(y + -2) = 4y ...

www.algebrahelp.com/calculators/equation/factoring/calc.do?equation=(y + 9)(y - 2) = 4y

Simplifying (y + 9)(y + -2) = 4y Reorder the terms: (9 + y)(y + -2) = 4y Reorder the ... solve: Simplifying -6 + -1y = 0 Solving -6 + -1y = 0 Move all terms containing y ...

Solve Radical Equation sqrt(x-9)=5 Tiger Algebra Solver

www.tiger-algebra.com/drill/sqrt(x-9)=5/

Step 3 : Solve the linear equation : Rearranged equation x -34 = 0. Add 34 to both sides x = 34. A possible solution is : x = 34 ...

Solve differential equation y'' + 4y' + 5 =0 - Mathematics Stack ...

math.stackexchange.com/questions/273295/solve-differential-equation-y-4y-5-0

Jan 9, 2013 ... Solve differential equation y'' + 4y' + 5 =0 ... So in this case m 2 + 4 m + 5 = 0. However I do not know what ... Dreamer78692 Jan 9 '13 at 5:11 ...

Linear Systems

jwilson.coe.uga.edu/emt668/EMAT6680.Folders/Barron/unit/Lesson 5/5.html

Specifically, we graphed the two equations y = 2x + 5 and y = (-3/2)x + 2, and noted that they shared the point ... To find y, substitute x = 3 into either equation as solve for y. .... What happens if you were asked to solve the equations: 3x + 7y = 9 and 2x + 7y = 10? ... Also, the point (0, 19/14) works, where x = 0 and y = 19/ 14.

Systems of Equations - Problems & Answers - Math

www.math10.com/en/algebra/systems-of-equation-problems.html

|x - y = 5 and |4x - 5y = 11 |2x + y = 9 ? Answer: No. (3-32) Solve the system of ... The solution is every couple, which is solution to the equation 4x - 3y - 2 = 0.

solve the system of equations 3x+2y=17, 2x-y=9? | Yahoo Answers

answers.yahoo.com/question/index?qid=20070521194511AAzMj3Q

May 21, 2007 ... 3x+2y=17- (1) 2x-y=9 - (2) Multiply 2nd equation by 2 and add it to the first. ... solve for y ( 2)- 2*5 - y = 9 -y = -1 y = 1. Joanne · 3 months ago. 0.

Find the Equation of a Line Parallel or Perpendicular to Another Line

www.mesacc.edu/~scotz47781/mat150/notes/eqn_line/Equation_Line_Parallel_Perpendicular_Notes.pdf

mx + b), which means we need to solve for y: The slope of the line 3x – 5y = 9 is m = 3/5. Therefore, the slope of the line parallel to this line would have to be m ...

Solve Simultaneous Equations By Elimination - Maths Accelerator

www.mathsaccelerator.com/algebra/simultaneous-equations-elimination

Solve Simultaneous Equations By Elimination ... 3x + 2y + 5 = 0 ... 9 = 0). 7x + 14 = 0 ... 4x + y = 9 8 + y = 9 y = 1. The simultaneous solution is x = 2 and y = 1. ... Remember that subtracting the second equation means that all signs of the second ...

How To Solve Y=mx+b - eNotes.com

www.enotes.com/homework-help/how-do-you-solve-graph-simple-y-mx-b-equation-61631

Posted on September 10, 2011 at 9:45 AM ... Consider the following example: actual equation y=2x+3 .... With this equation, 5 represents m, which is the slope, and the y-intercept is (0,6), which is given by b, OR by plugging 0 in for x. Then ...

More Info

How do you solve this equation y divided by 9 plus 5 equals 0

www.answers.com

Well it all depends on what you're actually asking. If you're asking about the equation: y/(9+5) = 0 then you would multiply each side by the.

Determine the slope and the y intercept of the graph of the equation ...

www.algebra.com

m= 0: no y intercept -9:(0,0) 1;(0,-9) 0;(0, -9) I am gong according to my book and this is what I did: y+9=0 y=0-9 y=-9 m=-9 ... y+9-9=0-9 [isolate the y-term to one side of the equation] y=-9. This is a ... The points will be (-2, -9) (0, -9) (5, -9), etc.

Systems of Linear Equations

www.columbia.edu

If x = 0, then f(0) = 25 - 5(0) = 25. If y = 0, then f(x) = 0 = 25 - 5x. 5x = 25. x = 5. The resulting ... Substitute this value for Q in either equation and solve for P. ... Step 3: Solve for y in either of the original equations. 2(-2) + 3y = 5. 3y = 9. y = 3 or.